Mechanisms in blood-brain barrier opening and metabolism-challenged cerebrovascular ischemia with emphasis on ischemic stroke - Sarvari, Sajad (Metab Brain Dis, 2020)
Stroke is the leading cause of disability among adults as well as the 2nd leading cause of death globally. Ischemic stroke accounts for about 85% of strokes, and currently, tissue plasminogen activator (tPA), whose therapeutic window is limited to up to 4.5 hours for the appropriate population, is the only FDA approved drug in practice and medicine. After a stroke, a cascade of pathophysiological events results in the opening of the blood-brain barrier (BBB) through which further complications, disabilities, and mortality are likely to threaten the patient’s health. Strikingly, tPA administration in eligible patients might cause hemorrhagic transformation and sustained damage to BBB integrity. One must, therefore, delineate upon stroke onset which cellular and molecular factors mediate BBB permeability as well as what key roles BBB rupture plays in the pathophysiology of stroke. In this review article, given our past findings of mechanisms underlying BBB opening in stroke animal models, we elucidate cellular, subcellular, and molecular factors involved in BBB permeability after ischemic stroke. The contribution of each factor to stroke severity and outcome is further discussed. Determinant factors in BBB permeability and stroke include mitochondria, miRNAs, matrix metalloproteinases (MMPs), immune cells, cytokines, chemokines, and adhesion proteins. Once these factors are interrogated and their roles in the pathophysiology of stroke are determined, novel targets for drug discovery and development can be uncovered in addition to novel therapeutic avenues for human stroke management.